Membuka Perspektif Guru Bahasa Inggris di Daerah Pedesaan tentang Alat Pembelajaran Digital - Boymau, Lusia Teodora; Sari Hidayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Educational transformation in rural areas faces various challenges, including limited access to diverse educational resources and inadequate technological infrastructure, which hinder the implementation of modern teaching methods. However, these obstacles can be overcome if teachers, as the leading actors, utilize the available learning resources. This study explores the perspectives on using digital learning tools among English teachers in rural contexts. It identifies barriers, opportunities, and implications for improving teaching practices and student learning in rural settings. Through a qualitative descriptive design, this study collected data by interviewing three English teachers from rural areas and analyzed the data using thematic analysis. The results showed that most teachers are aware of the potential of digital technology in improving learning effectiveness, especially in terms of broader access to materials and higher interactivity. However, the main challenges faced include limited technological infrastructure, lack of adequate training, and limited internet access, which hinder the optimal implementation of technology. Nevertheless, teachers remain enthusiastic about adopting digital tools, primarily if they are supported by government and educational institutions in training and providing better facilities. This study concludes that although digital learning tools have great potential to improve the quality of English learning in rural areas, their implementation still requires further attention related to technical factors and human resource readiness.